International pooled ana lysis of cancer incidence in children after assisted reproductive technologies: interim report. (August 2009) - Felix, Ashley S; Bruinsma, Fiona; Klemetti, Reija; Gissler, Mika; Lerner-Geva, Liat; Taioli, Emanuela
Aim: The aim of this study was to describe the process of pooling data from existing cohort studies of children born after assisted reproductive technologies (ART).Materials & methods: A comprehensive Medline search was performed to identify pertinent studies. Registers that collect follow-up data on children born after ART were identified. All authors and registers were contacted for participation.Results: Of the 48 potential sources of data for this analysis, 17 centers do not collect follow-up data on children born after ART, nor have cancer registries available in their country, two investigators refused to participate, four collaborators have sent their datasets, and six indicated agreement to participate, but have not sent their data yet. Follow-up time of the child was significantly variable between the cohorts, from 4.5 to 12 years. The total number of children enrolled by the studies participating in the pooled analysis is at least 33, 981.Conclusion: Our research shows that the current state of data collection in most countries is inadequate to fully address the issue of long-term safety of ART. The present pooling effort includes expansion of the cohort of children born after ART, updated record linkage for complete cancer cases identification and calculation of standardized incidence ratios, stratified by cause of infertility, socioeconomic status and hormonal regimen (as well as other confounders) to assess the long-term health status of children born after ART.